Pengaruh Servant Leadership Dan Spiritual Leadership Terhadap Motivasi Kerja Pegawai Pada Kantor UPTD PPD Kabupaten Kepahiang - Nelli Asvriana; Fahrudin JS Pareke; Wayan Dharmayana; Dwinda Agustintia (JURNAL WIRANOMIKA, 2023)
Work motivation has an important role in an organization, because with high work motivation it will increase work productivity for employees in carrying out their duties. The factors that influence work motivation are: human needs, compensation factors, communication factors, leadership factors, training factors, factors achievement. The leadership factor is one of the factors that affect the morale of the employees. The aims of this study are 1) To examine the effect of servant leadership and spiritual leadership together on employee motivation at the UPTD PPD office in Kepahiang Regency. 2) To examine the influence of servant leadership on employee work motivation at the UPTD PPD office in Kepahiang Regency. 3) To examine the influence of spiritual leadership on employee work motivation at the UPTD PPD office in Kepahiang Regency. The conclusions in this study are as follows: 1) The results of the study prove that servant leadership and spiritual leadership have a positive and significant effect on work motivation at the UPTD PPD Office, Kepahiang Regency by 48.3%, meaning that by applying servant leadership and spiritual leadership styles at the UPTD PPD Office Kepahiang Regency can increase work motivation and if the leadership always pays attention to and applies servant leadership and spiritual leadership styles, work motivation will continue to increase. 2) The results of the study prove that servant leadership has a positive and significant effect on work motivation at the UPTD PPD Office in Kepahiang Regency by 22.8%, meaning that by applying the servant leadership style at the UPTD PPD Kepahiang Office, it can increase work motivation and if the leadership always pays attention and applies this style. servant leadership, work motivation will continue to increase. 3) The results of the study prove that spiritual leadership has a positive and significant effect on work motivation at the UPTD PPD Office in Kepahiang Regency by 54.3%, meaning that by applying the spiritual leadership style at the UPTD PPD Kepahiang Office, it can increase work motivation and if the leadership always pays attention and applies this style. spiritual leadership, work motivation will continue to increase.Â Keywords: Servant Leadership, Spiritual Leadership, Work MotivationÂ